Unacceptable variation in abdominoperineal excision rates for rectal cancer: time to intervene?. Issue 12 (5th June 2008) - Morris, E; Quirke, P; Thomas, J D; Fairley, L; Cottier, B; Forman, D
Abstract : Objective: To determine the variation in the rates of use of abdominoperineal excision (APE) by cancer network, hospital trust and surgeon across England between 1998 and 2004 and determine if any variation could be explained by differences in patient characteristics such as stage of disease, age, gender or socioeconomic deprivation. Design: Retrospective study of a population-based dataset comprised of cancer registry and hospital episode statistics data. Setting: All NHS providers of rectal cancer surgery within England. Patients: 31 223 patients diagnosed with rectal cancer and receiving a major abdominal procedure within the NHS in England between 1998 and 2004. Main outcome measure: Rates and odds of use of APE were determined in relation to patient case-mix and each patient's managing surgeon, trust and cancer network. Results: The rate of use of APE decreased from 30.5% in 1998 to 23.0% in 2004. Males, the economically deprived and those managed by surgeons operating on fewer than seven rectal cancer cases per year were all significantly more likely to receive an APE. There were also significant variations in the odds of receiving an APE over time and between individual surgeons and hospital trusts independently of patient case-mix. Conclusions: Over the study period the use of APE decreased but statistically significant variation was observed in its application independently of case mix. Reducing this variation will remove inequalities, reduce colostomy rates, and improve outcomes in rectal cancer. Rates of APE use could be a national performance measure.